"What would Jesus play?": actor-centered perspectives on gaming and gamers (in lieu of an Introduction) - Heidbrink, Simone; Knoll, Tobias; Wysocki, Jan (Online - Heidelberg journal of religions on the internet, 2015)
Using the example of the US American Christian initiative GameChurch and their goals and activities in the context of digital games, the authors emphasize the significance of applying an actor-centered perspective on the research of digital gamers and the socio-cultural practice of ‘gaming’. While game-immanent topics might be the most obvious area of study, the focus on gamers and their in-game conduct offers exceptionally deep insights into the interconnections of in-game content with the religious disposition of the gamers. Thus, an actor-centered approach can generate important new data and perspectives for the analysis of contemporary (religious) meaning-making processes within individual and group-based pop-cultural contexts.
Keywords: Christ; Spieler; Computerspiel